Continuous Care Provided Through Comprehensive Medication Management in an Acute Care Practice Model. Issue 4 (April 2018) - Marr, T. David; Pinelli, Nicole R.; Jarmul, Jamie A.; Waldron, Kayla M.; Eckel, Stephen F.; Cicci, Jonathan D.; Bates, Jill S.; Amerine, Lindsey B.
Background: Pharmacy practice models that foster pharmacists' accountability for medication-related outcomes are imperative for the profession. Comprehensive medication management (CMM) is an opportunity to advance patient care.Objective: The objective of this study was to evaluate the impact of a CMM practice model in the acute care setting on organizational, patient, and financial outcomes.Methods: Three adult service lines focused on at-risk patients identified using internal risk stratification methodology were implemented. Core CMM elements included medication reconciliation, differentiated clinical pharmacy services, inpatient MTM consultations, discharge services, and documentation. Mixed methods compared the effect of the CMM model before and after implementation. Historical patients served as comparative controls in an observational design. Pharmacists completed a 60-minute interview regarding their experiences. Qualitative data were analyzed using thematic coding to characterize perception of the model.Results: Three pharmacists implemented the model on cardiology, hematology/oncology, and surgery transplant services and provided services to 75 patients during the study. A total of 145 medication-related problems were identified and resolved. CMM was associated with a nonsignificant reduction of 8.8% in 30-day hospital readmission rates ( P = 0.64) and a 24.9% reduction in 30-day hospital utilization ( P = 0.41) as well as a significant reduction of 86.5% in emergency department visits ( P = 0.02). Patients receiving discharge prescriptions from our outpatient pharmacies increased by 21.4%, resulting in an 11.3% increase in discharge prescription capture and additional revenue of 5780. Themes identified from qualitative interviews included CMM structure, challenges, value, and resources.Conclusion: This study demonstrated successful implementation of a CMM model that positively affected organizational, patient, and financial outcomes.